An unusual cause of significantly elevated blood alpha-fetoprotein levels: a case report and literature review - Zheng, Yue; Yao, Jianping; Liu, Jin; Zhao, Feimin (Frontiers in Oncology, 2024)
Alpha-fetoprotein (AFP) serves as a crucial diagnostic marker for primary hepatocellular carcinoma (HCC) and germ cell tumors (GCTs), with rare instances of significantly elevated levels in other diseases. In this study, we present a case of an elderly patient who was diagnosed with AFP-producing gastric cancer (AFPGC) following an elevated AFP result during physical examination. In investigating liver cancer at an early stage, the diagnosis was missed because of failure in detecting the lesion, resulting in delayed treatment initiation. AFPGC is a rare aggressive tumor that demands heightened awareness among clinicians to foster early detection, diagnosis, and treatment for improved prognosis.